al-Attas’ philosophy of history on the arrival and proliferation of Islam in the Malay world - Azmul Fahimi Kamaruzaman,; Aidil Farina Omar,; Roziah Sidik @ Mat Side, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
This article examines the philosophy of history of Syed Muhammad Naquib al-Attas on the theory of the arrival and spread of Islam in the Malay world, particularly in his work ‘Historical Facts and Fictions’. This philosophy of history is consequent to al-Attas' critical research contained in his previous works such as ‘Preliminary Statement on a General Theory of The Islamization of the Malay-Indonesian Archipelago’ (1969), ‘Islam in the Malay History and Culture’ (1972) and ‘The Correct Date of the Terengganu Inscription’ (1972). This study analyses these works and his other works to look into the aspects of history and historiography contained in the philosophy of history of al-Attas on the arrival and spread of Islam in the Malay world in terms of their scope, sources and history methods. This study found that in terms of epistemology al-Attas has contributed in creating a theoretical framework and a novel approach to the philosophy of history of the history of Islam in the Malay world.